2018
DOI: 10.1016/j.dld.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

HEPACONTROL. A program that reduces early readmissions, mortality at 60 days, and healthcare costs in decompensated cirrhosis

Abstract: HEPACONTROL decreases the incidence of early readmission the rate of emergency department visits and mortality at 60days in patients with decompensated cirrhosis, and it is cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 26 publications
(32 reference statements)
1
37
0
Order By: Relevance
“…Reduced guideline compliance has been associated with poor outcomes, including readmissions for overdiuresis, delayed hepatocellular carcinoma (HCC) diagnosis, reduced curative HCC treatment and increased oesophageal variceal haemorrhage 6 10 12. Quality improvement studies of decompensated cirrhosis have demonstrated improved patient outcomes by increasing practice guideline adherence 13–17. An estimated 22% of readmissions for decompensated cirrhosis could have been prevented, in many cases by closer adherence to evidence-based guidelines 6…”
Section: Introductionmentioning
confidence: 99%
“…Reduced guideline compliance has been associated with poor outcomes, including readmissions for overdiuresis, delayed hepatocellular carcinoma (HCC) diagnosis, reduced curative HCC treatment and increased oesophageal variceal haemorrhage 6 10 12. Quality improvement studies of decompensated cirrhosis have demonstrated improved patient outcomes by increasing practice guideline adherence 13–17. An estimated 22% of readmissions for decompensated cirrhosis could have been prevented, in many cases by closer adherence to evidence-based guidelines 6…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing factors associated with readmission and increased cost is crucial in order to reduce subsequent readmissions, hospital costs, morality, and ultimately improve quality of life. While age is a non-modifiable risk factors and insurance provider is challenging to modify, these patients should be targeted for interventions that are proven to reduce readmission rates, including a call from healthcare provider, early outpatient follow up and providing patients with enough supply of medications prior to discharge[ 28 , 29 ]. Patients that undergo frequent paracentesis should be evaluated early for other interventions, such as a transjugular intrahepatic portosystemic shunt (TIPS) or liver transplantation in order to prevent frequent readmission and costs associated with frequent large volume paracentesis[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…(7,(89)(90)(91)(92)(93)(94) Most involved implementation of new multidisciplinary "chronic disease management" models or "patient care management" programs to improve postdischarge care and prevent readmission. Three studies delivered face-to-face interventions (89,92,93) and two studies used modern technologies (90,91) to assist with remote management of medications and liver disease complications. While outcome measures varied, most studies reported reduced readmission rates (including for potentially medication-preventable complications, like ascites and HE) but not medication-specific outcome measures, like adherence or MRPs.…”
Section: Patient-oriented Interventionmentioning
confidence: 99%
“…A small number of patient‐oriented interventions that mention a dedicated medication component have been conducted in people with cirrhosis (Table 3). ( 7,89‐94 ) Most involved implementation of new multidisciplinary “chronic disease management” models or “patient care management” programs to improve postdischarge care and prevent readmission. Three studies delivered face‐to‐face interventions ( 89,92,93 ) and two studies used modern technologies ( 90,91 ) to assist with remote management of medications and liver disease complications.…”
Section: Patient‐related Factorsmentioning
confidence: 99%